Isolation and characterization of bacteriophages with lytic activity against multidrug-resistant non-typhoidal Salmonella from Nairobi City county, Kenya - Mugo, M.; Musyoki, A.; Makumi, Angela; Mutai, I.; Kering, K.; Muturi, P.; Kebenei, C.; Weber, K.; Pietsch, M.; Pilz, T.; Drechsel, O.; Hoffmann, T.; et al. (BioMed Central, 2025)
Background: Non-typhoidal Salmonella (NTS) typically cause self-limiting enterocolitis, but can lead to life-threatening invasive diseases, particularly in sub-Saharan Africa. In Kenya, multidrug-resistant (MDR) NTS strains with increasing non-susceptibility to third-generation cephalosporins pose a growing public health threat. As traditional antimicrobial treatments become less effective, bacteriophages are emerging as a potential alternative. This study aimed to isolate and characterize bacteriophages targeting MDR and extended spectrum-β-lactamase (ESBL)-producing non-typhoidal Salmonella (NTS).